2018
DOI: 10.12775/ra.2017.015
|View full text |Cite
|
Sign up to set email alerts
|

Przyjmowanie leków w późnej dorosłości – potrzeba edukacji zdrowotnej

Abstract: Przyjmowanie leków w późnej dorosłości -potrzeba edukacji zdrowotnejMedication use in the elderly -the need for health educationStreszczenie. Ogólnoświatowy trend wskazujący na rosnącą oczekiwaną długość życia i wzrost w demograficznej strukturze wielu społeczeństw odsetka osób w wieku emerytalnym powoduje, iż edukacja zdrowotna seniorów stanowi obecnie niezwykle ważne zagadnienie. Niewystarczające przygotowanie do zapobiegania i radzenia sobie z licznie występujący-mi w zaawansowanym wieku zagrożeniami sygnal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 6 publications
(3 reference statements)
0
4
0
Order By: Relevance
“…Important information can also be found on the packaging of preparations. The key information ensuring the safety and quality of the preparation is the expiration date, so it is worth checking your medicines in this respect [3,31]. This study shows that finding it is not a problem for patients, and its form is understandable to them, as well as for instructions on the possible time of use of the preparation.…”
Section: The Impact Of Training Led By Students On the Level Of Knowl...mentioning
confidence: 91%
See 3 more Smart Citations
“…Important information can also be found on the packaging of preparations. The key information ensuring the safety and quality of the preparation is the expiration date, so it is worth checking your medicines in this respect [3,31]. This study shows that finding it is not a problem for patients, and its form is understandable to them, as well as for instructions on the possible time of use of the preparation.…”
Section: The Impact Of Training Led By Students On the Level Of Knowl...mentioning
confidence: 91%
“…The study showed that after the training, the level of knowledge could significantly improve, and the multimedia form of the lecture is as effective as possible for this purpose, also in discussing the issue of an expired drug and giving it to the pharmacy. This is a very important and common problem because the drug is a specific type of waste that is hazardous and must be properly disposed of [31].…”
Section: The Impact Of Training Led By Students On the Level Of Knowl...mentioning
confidence: 99%
See 2 more Smart Citations